Thermomechanical modelling of lithospheric slab tearing and its topographic response - Boonma, Kittiphon; García-Castellanos, Daniel; Jiménez-Munt, Ivone; Gerya, Taras (Frontiers in Earth Science, 2023)
Lithospheric slab tearing, the process by which a subducted lithospheric plate is torn apart and sinks into the Earth’s mantle, has been proposed as a cause for surface vertical motions in excess of 100’s of meters. However, little is known about the mechanisms that help initiate and control the propagation of slab tearing and the associated uplift. This study aims to explore these processes by means of 3D thermo-mechanical geodynamic modelling of a slab retreat oblique to a continental margin, using the Gibraltar Arc region (Betic Cordillera) as a scenario for inspiration. Our results suggest that the obliquity of the continental passive margin relative to the subduction trench leads to an asymmetric distribution of subduction forces and strength, facilitating the initiation of slab tearing. The model results predict a lateral migration of the tearing point at a velocity ranging between 38–68 cm/yr for a sublithospheric-mantle viscosity of up to 1e+22 Pa·s. This fast slab tearing propagation yields uplift rates of 0.23–2.16 mm/yr above the areas where the subducted slab is torn apart, depending on mantle viscosity. Although a more detailed parametric exploration is needed, this range of uplift rates is compatible with the uplift rates required to overcome seaway erosion along the Atlantic-Mediterranean marine corridors during the Late Miocene, as proposed for the onset of the Messinian Salinity Crisis.